2011
DOI: 10.3174/ajnr.a2363
|View full text |Cite
|
Sign up to set email alerts
|

Angioplasty and Stenting of Atherosclerotic Middle Cerebral Arteries with Wingspan: Evaluation of Clinical Outcome, Restenosis, and Procedure Outcome

Abstract: BACKGROUND AND PURPOSE:MCA is a common location of intracranial stenosis. It is relatively more peripherally located and of a smaller caliber, and could therefore be a site technically more challenging and risky for angioplasty and stenting. The study aimed to evaluate the clinical outcome, restenosis rate, and procedural safety of Wingspan stent placement for atherosclerosis in the MCA compared with stenosis in other arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…it also carries a substantial risk of procedure-related cerebrovascular events, including thrombotic stroke, intracranial hemorrhage and even death [3][4][5][6][7][8][9] . The recent study of the Stenting and Aggressive Medical Management for Preventing Recurrent Stroke (SAMMPRIS) study 3, 10 demonstrated higher perioperative and 2-year cumulative stroke rates than medications alone, but this study is only one of the many trials in the initial stage of the Wingspan (Stryker Neurovascular, Fremont, CA, USA) stenting for intracranial atherosclerotic stenosis.…”
mentioning
confidence: 99%
“…it also carries a substantial risk of procedure-related cerebrovascular events, including thrombotic stroke, intracranial hemorrhage and even death [3][4][5][6][7][8][9] . The recent study of the Stenting and Aggressive Medical Management for Preventing Recurrent Stroke (SAMMPRIS) study 3, 10 demonstrated higher perioperative and 2-year cumulative stroke rates than medications alone, but this study is only one of the many trials in the initial stage of the Wingspan (Stryker Neurovascular, Fremont, CA, USA) stenting for intracranial atherosclerotic stenosis.…”
mentioning
confidence: 99%
“…2,3 During the past decade, percutaneous transluminal angioplasty and stenting (PTAS) has been evolving as a possible treatment option for ICAS patients at particularly high risk for recurrent stroke. 1,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] However, a higher risk of major complications including periprocedural stroke or death and intracranial in-stent restenosis (ISR) limited its use in clinical practice. Only when those 2 are controlled to an enough small rate will PTAS be a promising option for symptomatic ICAS.…”
mentioning
confidence: 99%
“…Patients who subsequently underwent angioplasty and stenting fulfilled the criteria as described elsewhere [12]. In brief, these patients had symptomatic intracranial stenosis ≥70% or stenosis ≥50% with recurrent ischemia despite medical therapy, and the diameter of vessel immediately adjacent to the stenosis was ≥2 mm.…”
Section: Methodsmentioning
confidence: 99%